A Critique on the Book Silent Cinema by Liam O’Leary, Paul A. Schroeder Rodriguez, translated by Majid Mostafavi - Hamed Fardar; Hamid Dehghanpour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The history of silent cinema is, in one sense, a record of the struggles, sufferings, victories, and failures that have been instrumental in achieving what we know today as cinema and its rules and attributes. It is also about the historical narratives that have been polished and expanded our understanding of the silent era over time. This book is a combination of two separate books by Liam Olieri and Paul Schroder Rodriguez, a concise, compelling narrative of those early years. The first book, by Liam Olivier, is dedicated to the history of silent cinema in Western countries, and the second, written by Paul Rodrigues, analyses the history of that time in Latin America. This article attempts to look at the omissions and shortcomings of the book in the Persian version to show which parts of it are repetitive and inconsistent and which ones are useful, fresh, and informative for readers.